Analisis Potensi Daya Mekanis Yang Dihasilkan Konverter Energi Metode Bandul Vertikal Di Air Tenang - Hendri Suryanto; Drajat Indah Mawarni (SIMETRIS, 2019)
Hydroelectric power plants have been widely developed. One that is mostly built especially in mountainous or highland areas is power plants that use falling water energy or river water currents to turn turbines connected to generators. In coastal areas today power plants have been developed using abundant sea waves known as the Wave Energy Converter (WEC), with one of the methods used is the pendulum method. For areas in the lowlands and far from the coast but there are bodies of water such as lakes, swamps and rivers with slow flow, which are large enough, the potential of the water has not been used to drive electricity generation and the question arises whether it can be utilized to drive the converter. For this reason, it is necessary to research the use of calm water to drive the converter. By adopting the WEC technology used in ocean waves, the vertical pendulum method above the pontoon was chosen in this study, which according to the author's consideration is simpler than the other methods. The design of the converter made was a vertical pendulum mounted on a flat pontoon by adding components in the form of a barrier pair to make water surging continuously under the pontoon so that the pendulum swings continuously. In this study the observed variable was the power produced by the converter by varying the arm length from 0.2 to 0.3 m with a pendulum load varying from 0.5 to 1 kg. Theoretical analysis showed the results of greater mechanical power produced by using a larger pendulum mass. And the faster rotation of the pendulum shaft was produced by using the shorter pendulum arm.